Desenvolvimento profissional de formadores em exercício: contribuições de um programa online - Rinaldi, Renata Portela (2009)
This research tries to understand the contributions of an online continuous formation Program, aiming at the professional development of formers working with basic education, supported by the theoretic-methodological reference of professional practice epistemology and distance education. Thematics such as teachers formation and distance education were examined, more specifically the online education , for considering the distance education strategy, linked to information and communication technologies (ICT), a way to conceive new opportunities for the professional development, viewing school as the formation process center references were form Shulman, 1986, 1987; Pérez Gómez, 1989; Zeichner, 1993, 2008; Knowles and Cole, 1995; Tardif, 2000, 2002; Prado and Valente, 2002; Almeida, 2003, 2005; Mizukami et al, 2003; Moran, 2003; Vaillant, 2003; Schlemmer, 2005; Vaillant and Marcelo, 2006; Hunt, 2008. The methodology used was based on the constructive collaborative pattern of research-intervention, [Cole and Knowles, 1993; Mizukami et al, 2003] linked to qualitative research theoretical matrix [Bogdan and Bicklen, 1994; Lüdke and André, 1986]. The intervention research was characterized by an online professional development Program, in the digital learning environment of the UFSCar Teachers Portal, with the participation of sixteen formers working with basic education and two researches acting as the Program mediators. The analyses were draw out from the formers reports in varied activities, such as debates occurred throughout the formative processes, private messages (mail) and testimonies that produced the formers reflexive memorial at the end of the Program. The results try to clear up aspects related to the work configuration during time spent in the learning digital situation, indicating different moments by which formers passed by in this professional development process and through the building-up of confidence relation ships, when doubts, anguishes, fears, certitudes and convictions that orientate their practices start to be explicit collectively, offering the opportunity of thinking in and about the practice from a sharing glance, allowing then the no-knowing explicit and the possibility of negotiating and explicit senses to become a former in basic education. Such dynamics happened because of the researchers continuous presence, which helped to approximate formers and to create affective bonds, which assume in the digital context a more complex dimension, related to subjective questions, due to thought expression and communication based on writing. Besides, results showed traces of how the formers knowledge changed during the process, from the concepts they have about their profession and the meaning of being a former, and relationships set up with the school partners, the theoretical discussions about how to teach teachers to teach, the possibilities of keeping on learning despite the adversities of their profession and the function/charge they occupy. Therein, it is possible to understand this researchintervention as an investigation that passes through the formation universe of online education and professional practice, that bring together results that amplify the debate about how elaborate continued formation processes in apprenticeship digital contexts, having the school as its center. In placing the basic education formers as the focus of the study, this research also came across results that enlarge the rare existing reflections about teachers formers, mainly because are being focused the basic education professionals, which also offer outpoints for debates and new researches interested in increasing knowledge in this promising investigative front.